Dynamic Changes in Natural Killer Cell Subset Frequencies in the Absence of Cytomegalovirus Infection - Gyurova, Ivayla E.; Schlums, Heinrich; Sucharew, Heidi; Ambroggio, Lilliam; Ochayon, David E.; Win, Hannah Than; Bryceson, Yenan T.; Bernstein, David I.; Waggoner, Stephen N. (Frontiers in Immunology, 2019)
Individuals lacking functional natural killer (NK) cells suffer severe, recurrent infections with cytomegalovirus (CMV), highlighting the critical role of NK cells in antiviral defense. Therefore, ongoing attempts to develop an efficacious vaccine to prevent CMV infection should potentially aim to elicit NK-cell antiviral responses as an accessory to conventional T- and B-cell based approaches. In this regard, CMV infection provokes marked phenotypic and functional differentiation of the NK-cell compartment, including development of adaptive NK cells that exhibit enhanced antiviral activity. We examined longitudinal blood samples collected from 40 CMV-seronegative adolescents to ascertain whether a CMV glycoprotein B (gB) vaccine in the absence of CMV infection can stimulate differentiation or expansion of CMV-associated subsets of NK cells. Study participants uniformly lacked the CMV-dependent NKG2C+ subset of NK cells, suggesting that an adjuvanted CMV gB vaccine alone is an inadequate stimulus for sustained expansion of these cells. In contrast, we observed unexpected dynamic fluctuations in the frequency of NK cells lacking FcRg, EAT-2, and SYK, which were independent of vaccination or CMV infection. Whereas FcRg-neg NK cells in CMV infection are reported to express increased levels of the maturation marker CD57, the FcRg-neg NK cells observed in our CMV-negative vaccine cohort express less CD57 than their FcRg+ counterparts. The FcRg-neg NK cells in CMV-negative individuals were also functionally distinct from this subset in CMV infection, exhibiting comparable IFN-g production and degranulation as FcRg+ NK cells in response to cytokine or antibody-dependent stimuli. These results suggest that frequencies of some NK cell subsets may increase in response to unknown environmental or inflammatory cues distinct from that which occurs after CMV infection. Greater understanding of the nature of the signals driving CMV-independent accumulation of these subsets should permit development of mechanisms to facilitate vaccine-driven expansion of CMV-reactive NK cells.